Determinants of transmission prevention behavior among Tuberculosis patients in Surabaya, Indonesia - Ni Njoman Juliasih; Luluk Fadhoh Sakinah; Reny Mareta Sari; Hudi Winarso; Salmon Charles P.T. Siahaan; Erik Jaya Gunawan (Elsevier, 2024)
Background: Tuberculosis (TB) is associated with significant morbidity and mortality, causing significant health challenges globally. Meanwhile, Indonesia ranks second worldwide in terms of TB prevalence, with East Java being among the most affected provinces. Surabaya, in particular, a major city reported approximately 4.628 cases in 2021, underscoring the urgent need to prevent transmission through behavior of patients. Therefore, this study aimed to analyze determinants of transmission behavior among TB patients in Surabaya, Indonesia. Methods: The methodology used in this study was a cross-sectional design and the participants were 144 TB patients at three community health centers in Surabaya, selected using simple random sampling. Variables including knowledge level, supportive behavior, and medication adherence were analyzed and data collection was carried out using a structured questionnaire. Additionally, data analysis was performed with statistical methods to determine the significance of variables. Results: The results showed that knowledge (P-value = <0.001), supportive behavior (P-value = 0.001), and medication adherence (P-value = 0.004) had a significant effect on transmission prevention behavior among TB patients. Conclusion: Based on our results, it was concluded that higher knowledge level, supportive behavior, and medication adherence had a significant correlation with increased social support provided by patients in preventing and controlling TB transmission. Therefore, there is a need to implement targeted programs to enhance prevention behavior.